2021
DOI: 10.1016/j.ijid.2020.11.129
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the Mycobacterium tuberculosis complex strains from newly diagnosed tuberculosis patients in Northwest Ethiopia reveals a predominance of East-African-Indian and Euro-American lineages

Abstract: This study described the population structure of M. tuberculosis complex (MTBc) strains among patients with pulmonary or lymph node tuberculosis (TB) in Northwest Ethiopia and tested the performance of culture isolation and MPT64-based speciation for Lineage 7 (L7). Methods: Patients were recruited between April 2017 and June 2019 in North Gondar, Ethiopia. The MPT64 assay was used to confirm MTBc, and spoligotyping was used to characterize mycobacterial lineages. Line probe assay (LPA) was used to detect resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 53 publications
5
9
0
Order By: Relevance
“…Strains of L4 and L3 are the main causative agents of TB comprising 55.8% and 25.7% of the investigated strains, respectively. These findings mirror reports from neighboring countries, such as Ethiopia [ 33 ], Tanzania [ 34 ], and Uganda [ 35 ] but are in contrast to the findings from Shuaib et al [ 12 ] and Ejo et al [ 36 ] in Eastern Sudan and Northwest Ethiopia where L3 strains were the main etiological agent of TB.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Strains of L4 and L3 are the main causative agents of TB comprising 55.8% and 25.7% of the investigated strains, respectively. These findings mirror reports from neighboring countries, such as Ethiopia [ 33 ], Tanzania [ 34 ], and Uganda [ 35 ] but are in contrast to the findings from Shuaib et al [ 12 ] and Ejo et al [ 36 ] in Eastern Sudan and Northwest Ethiopia where L3 strains were the main etiological agent of TB.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, the high prevalence of the strains of the generalist LAM sublineage might explain the dominance of L4 strains in Nairobi in Kenya. Another possible explanation for the success of L4 might be related to the observation that some L4 strains are capable of evading the host immune response and rapidly progressing to TB disease and thus are more often transmitted [ 15 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the INH mono-resistance was predominantly identified in the T3-ETH sublineage. Previous studies from Ethiopia conducted using direct spoligotyping have also reported similar detection rates of INH monoresistant isolates belonged to diverse families within Euro-American (L4) [37]. As a consequence, it is necessary to develop a closer surveillance system in the country, with a particular emphasis on isolates where resistance to isoniazid is observed, and to reduce the evolution of DR to MDR and subsequent dispersion within the population.…”
Section: Discussionmentioning
confidence: 95%
“…Molecular genotyping tools, like spoligotyping and other PCR-based sequencing methods, help us to understand MTBC epidemiology in a specific geographical region, predict disease transmission, and identify prominent genotypes and TB strains that are likely to spread [ 19 ]. The genetic diversity and geographic distribution of MTB lineages have been studied across different settings and regions of Ethiopia [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] ] and revealed the presence of diverse MTBC sublineages. The Ethiopian-specific lineage (SIT149/T3-ETH sublineages) was reported as a predominant TB strain in the country [ 25 , [31] , [32] , [33] , [34] , [35] ], while lineage 3/CAS1-DELHI sublineages was another widespread strain in certain regions of Ethiopia [ 20 , 26 , 27 , 36 ].…”
Section: Introductionmentioning
confidence: 99%